Kinetics and Isotherm Study of Ion Phosphate Adsorption by Lontor Natural Clay - Ikhsan, Nurul; Sekewael, Serly J; Hasanela, Nurani (Indonesian Journal of Chemical Research, 2022)
The clay used taken from Lontor Village, Central Maluku Regency, Banda Besar Island. The clay was activated at 350 °C for 3 hours using a furnace. This study aims to determine the effectiveness of physically activated Lontor natural clay in reducing levels of phosphate ions using the adsorption method. The adsorption capacity of clay is determined based on two parameters. The parameters are the optimum contact time used are 2, 3, 4, 5, and 6 hours and variations of the concentration are 10, 20, 30, 40, and 50 mg/L of phosphate. The concentration of phosphate adsorbed on the clay was measured by a UV-Vis spectrophotometer at a wavelength of 665 nm. The results showed that the optimum conditions for the adsorption of phosphate ions by Lontor natural clay were obtained at the contact time of 5 hours and the concentration of 40 mg/L. The adsorption of phosphate ions by Lontor activated natural clay followed the pseudo-second-order Lagergren adsorption kinetics model with a rate constant value (k2) of 3.39 x 10-1 g mg-1 min-1, and following the Freundlich adsorption isotherm models with a correlation coefficient (R2), Freundlich constant (Kf), and n values, respectively are 0.9513; 0.57 mg1-1/n L1/n/g, and 0.40 g/L.